ICT Application as A Supervisory Tool for Effective Instructional Delivery Approach for Secondary Schools in Kwara State - Yahaya, Ajoke Kudirat; Bolaji, Hameed Olalekan (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
Information and communication technology (ICT) has become an integral part of modern society, and its applications are not limited to the business and industry sectors alone. The effective use of ICT in schools depends on the availability of appropriate infrastructure and resources. The current research aims to examine the extent to which ICT tools enhance the effectiveness of instructional delivery in secondary schools in Kwara State. This study used a survey research method to conduct a systematic inquiry into a subject. Five research questions will guide the study using qualitative data collection methods. The study will be conducted in three randomly selected secondary schools in Kwara State with a sample of 150 teachers and 60 school leaders participating. The questionnaire used was titled ICT Applications as supervisory tools for effective instructional delivery. The qualitative data will be collected through in-depth interviews with 150 teachers and 60 school administrators in the selected schools. The findings advocate that ICTs have the potential to improve the quality of education and enhance the learning experiences of students. The study also highlights the challenges that teachers face in the use of ICT and the need for the government and other stakeholders to address these challenges to ensure the effective use of ICTs in education.